PETROGRAPHY AND GEOCHEMICAL CHARACTERIZATIONS OF TANAWAL FORMATION (QUARTZOSE ROCKS FROM SWABI, KHYBER PAKHTUNKHWA, PAKISTAN; IMPLICATIONS FOR INDUSTRIAL SUITABILITY - Muhammad Naveed Anjum; Muhammad Yaseen; Jawad Ahmad; Ihtisham Islam (Spectrum of Engineering Sciences, 2025)
The quartzose rocks of the Tanawal Formation, exposed in Topi area, district Swabi, in Khyber Pakhtunkhwa, Pakistan. This study evaluates the studied rocks for their suitability in glass and other industries using the techniques of petrography and geochemistry. Field observations and petrographic data leads to distinction of Tanawal Formation into two discrete lithologies a) Blasto-psammites and b) Blasto-pelites. These rocks have been slightly metamorphosed and foliation planes are well developed especially in pelitic rocks. In blasto-psammites quartz, feldspars, micas, ore minerals with minor amount of tourmalines and zircon occur as the framework minerals, while in pelitic rocks quartz and micas occurs as framework minerals. Blasto-psammites have variable modal percentage of quartz (93－94%) but most of the samples fall in quartz arenite (quartzite) and sub-arkoses field in Quartz－Feldspar－Lithics (QFL) ternary diagram. Petrographic data revealed that all of the studied samples are very fine to medium grained quartzose rocks. A very low grade metamorphic event has slightly obliterated the original sedimentary fabric of these rocks but most of these are still intact. Quartz grains are present in monocrystalline as well as polycrystalline form. Geochemical analysis of the Tanawal Quartzite indicates high contents of SiO 2 (93－94 %) and fairly low percentage of other major oxide i.e MgO (0.023 wt.%), Na 2 O (2.92 wt.%), K 2 O (0.52 wt. %) thus endorsing their quartz--rich mineralogy.Both petrographic and geochemical data reveal that the studied rocks lie within the range of standard specifications required for glass industries (i.e SiO 2 93－94%). The rocks are declared suitable for the manufacturing of low quality glass products i.e. soda-lime glass, flint glass, amber glass, green glass and glass-fiber insulation